2007
DOI: 10.1002/jcc.20781
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and physical properties of MiXi clusters (M = B, Al; X = N, P; i = 1, 2, 3): Ab initio study

Abstract: Ab initio calculations of structural stability and properties of selected IIIa-Va monomers (BN, BP, AlN, AlP), and dimers and trimers thereof are presented. It was demonstrated that multireference methods are needed for an appropriate description of the electronic structure of the diatomics under study. The energy differences between the quasi-degenerated states of monomers were determined: in the range of 220-257 cm(-1) for the X3Pi --> A1Sigma+ in BN, 277-311 cm(-1) for the X3Pi --> A3Sigma(-) in AlN, and 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The potential energy surface (PES) of NB 6 – suggested that the planar hexacoordinate nitrogen species NB 6 – is not stable . The structure and property of (BN) n ( n = 2−11) have been investigated theoretically,[] among which researchers found the stability of cyclic B 3 N 3 isomer with D 3h symmetry is ascribed mainly to its aromaticity . The structure and stability of (BN) n ( n = 2–4) were investigated by ab initio calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The potential energy surface (PES) of NB 6 – suggested that the planar hexacoordinate nitrogen species NB 6 – is not stable . The structure and property of (BN) n ( n = 2−11) have been investigated theoretically,[] among which researchers found the stability of cyclic B 3 N 3 isomer with D 3h symmetry is ascribed mainly to its aromaticity . The structure and stability of (BN) n ( n = 2–4) were investigated by ab initio calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the TSR mechanism can provide a pathway with low activation energy or alter the product composition and yield ratio. Oncák et al [12] studied the hydroxylation of alkanes by reagents HOF and HOCl in the gas phase upon acid catalysis but only singlet pathways were investigated (without considering TSR).…”
mentioning
confidence: 99%